2x+9=-47-6x

Simple and best practice solution for 2x+9=-47-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+9=-47-6x equation:


Simplifying
2x + 9 = -47 + -6x

Reorder the terms:
9 + 2x = -47 + -6x

Solving
9 + 2x = -47 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
9 + 2x + 6x = -47 + -6x + 6x

Combine like terms: 2x + 6x = 8x
9 + 8x = -47 + -6x + 6x

Combine like terms: -6x + 6x = 0
9 + 8x = -47 + 0
9 + 8x = -47

Add '-9' to each side of the equation.
9 + -9 + 8x = -47 + -9

Combine like terms: 9 + -9 = 0
0 + 8x = -47 + -9
8x = -47 + -9

Combine like terms: -47 + -9 = -56
8x = -56

Divide each side by '8'.
x = -7

Simplifying
x = -7

See similar equations:

| b-13=4 | | 20-6x=12-7x | | 2m+4=m+7 | | 6x-1+6x-6+82=180 | | 6x^2=34x-40 | | 20x^2-16x=4x | | 4w/7=56 | | -39=-22+d | | 4a^2+b^2+12a-4b+13=0 | | 6x^2-23=-21 | | 4+7x=-32+x | | 35=7/3w | | -36+8b=4(3+4b) | | a+23=25 | | (5x)+7=-2x | | 2c-10+6= | | -58x-2+6=8x-230.6 | | 262.818/28.26 | | x(2x-2)+x(2x-4)=(4x+7)(x-3) | | (2x^4+7x^3-8)-(7x^2-5x+4)= | | -2-5x=-2(1+4x) | | 1/2*b*19.8 | | 7g+8=22 | | 0.2x=-0.7 | | R=1-2n+5 | | 4x+4x+3=0 | | 14-12=x/-4 | | 5x/4-3=7x/6 | | 17-3(4-3x)=6x-1 | | (-2z/y^3)^2 | | 1/3(m-3n)=2 | | 3x(-5)/2x |

Equations solver categories